PENDIDIKAN KESEHATAN REPRODUKSI SEKSUAL TERHADAP TINGKAT PENGETAHUAN DAN SIKAP REMAJA SMA DI KECAMATAN TOSARI KABUPATEN PASURUAN (Pre-Ekspremental Study) - Fardiansyah, Arief; Solichati, Nur; Sudiyanto, Henry; Alamudi, Mohammad Yusuf (LPPM STIKES HUSADA JOMBANG, 2025)
Background: Sexual reproductive health education is a crucial effort in enhancing adolescent knowledge and attitudes towards reproductive health. Objectives: To analyze the effect of sexual reproductive health education on the level of knowledge and attitudes among adolescents in senior high schools (SMA) in Tosari District. Methods: This study employed a quantitative method with a pre-experimental design, utilizing the one-group pretest-posttest approach. This research will be conducted from March to June 2024. The research sample consisted of 250 students in grades X, XI, and XII who were taken as a whole or total population. The data collection instrument was a questionnaire that measured the level of knowledge and attitudes of adolescents before and after being given an intervention in the form of reproductive health education. Data analysis used the Wilcoxon Signed Rank Test to measure the significance of the difference between two groups of data, namely pretest and posttest data, both at the level of knowledge and attitudes. Results: There was a significant increase in the level of knowledge (p < 0.05) and positive changes in adolescent attitudes towards reproductive health after the intervention. This study shows that sexual reproductive health education has a significant influence on increasing adolescent knowledge and attitudes. Conclusion: Sexual reproductive health education programs should be integrated more widely in schools as part of the curriculum to help adolescents understand the importance of maintaining their reproductive health.